Management Model for Preventing Unwanted Pregnancy in Teenagers: A Systematic Review - Srisujarit, Duanghathai; Techakampholsarakit, Lalitwadee; Phongpate, Kantaporn (Nursing Journal of The Ministry of Public Health, 2021)
The purpose of this systematic review was to explore characteristics of studies focusing on management models for prevention of unwanted pregnancies among Thai teenagers and to summarize evidence-based knowledge derived from these studies. The seven research studies published during the year 2007-2018 in Thailand were selected from 501 studies. The data extraction method developed by the Joanna Briggs Institute (JBI) was used for data collection. Data were analyzed using descriptive statistics and content analysis. The results were as follows: all research studies reviewed in this study reached level 2C of the JBI. All of the samples in the studies were female teenagers. Management models for the prevention of unwanted pregnancies consisted of health education, motivation and behavioral skills. All management models for the prevention of unwanted pregnancies could improve knowledge and unwanted pregnancy prevention skills of study groups. This systematic research could be used to develop a management model for preventing unwanted pregnancy in teenagers by providing information positive motivation, and social support as well as improving skills to avoid sexual risk behaviors which can also help solving other health problems.